Deep Neck Infections among the Population Attending at Nobel Medical College Biratnagar - Suwal, Ravi Bhushan; Basnet, Meenakshi; Acharya, Rabin; Parajuli, Kamal (Journal of Nobel Medical College, 2015)
Introduction: The advent of diagnostic tools and antibiotic, incidence of deep neck infections have been reduced but still infections are seen today with definite potential for significant morbidity and mortality. The purpose of this study was to review predisposing factors, bacteriology, treatment and possible complications. Study design: A retrospective review was conducted of patients who were diagnosed as deep neck infections in Department of Otolaryngology at Nobel Medical College from between August 2010 to December 2014.Total 90 patients were included in this study. Their demography, etiology, underlying systemic diseases, infection locality, causative organism and modality of treatment were reviewed. Results: Of 90 patients, 65 were male and 25 were female. Fourty eight patients were in age range of 20-40 years and which was the most affected age group in our series. Odontogenic and parotid infections were the most frequent causes for deep neck infections. Submandibular space and cervical lymphnode were most affected site in neck. Staphylococcus aureus and mixed flora were organisms commonly isolated from culture. The most commonly found systemic diseases were diabetes mellitus and systemic arterial hypertension. In our series 18 patients (20%) had associated diabetes mellitus (DM).The most frequently encountered complication was upper airway obstruction. In our series 3 patients undergone tracheostomy; one patient each with Ludwig’s angina, necrotizing fasciitis and retropharyngeal abscess. Conclusions: It is essential to pay attention to older patients associated with systemic diseases (DM, HTN, Chronic kidney disease), because they can often progress to life threatening complications. The mainstays of treatment are maintenance of the airway, fluid resuscitation, intravenous antibiotics, and timely adequate surgical drainage. Therapeutic needle aspiration and conservative medical treatment are effective in selective cases such as those with minimal abscess formation. Journal of Nobel College of Medicine Vol.4(1) 2015: 26-31